Meningkatkan Kemampuan Aplikasi Logika Matematika Melalui Pendekatan Realistik Di SMAN 19 Bekasi - Rifki Ristiawan (SAP (Susunan Artikel Pendidikan), 2018)
Student’s application skill is something that must be improved in learning mathematics. The lack of relevance of some mathematics teaching materials such as mathematical logic in schools with daily life of students often creates a weakness in mathematics education. This situation encourages an idea that mathematics learning should be contextual. One of alternatives estimated to be able to improve student’s application skill is a realistic learning approach. This research is a classroom action research on the 20 students of class X.1 in SMAN 19 of academic year 2012/2013 in Bekasi regency. The results obtained are: (a) students’ activities have increased in each cycle, with the highest percentage of activity in cycle 3 of 85.26%. While the teacher's activities during the learning process are always based on the planned learning stages. (b) students' application skill before applying realistic learning approach is 31.85%, indicating a very low criterion. (c) The average student’s logic application skill in cycle 1 is 65.42% with enough criterion, cycle 2 is 70,6% with enough criterion, and cycle 3 is 76,10% with high criterion. (c) students’ application skill after applying realistic learning approach shows a high criterion of 75.85% and experiences 44% increase from student’s application before before learning.